Maternal and neonatal outcomes in teenage pregnancy: an observational study from Odisha - Nepak, Arabinda; Soren, Surendra Nath; Karjee, Ashish Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: With changing socio-demographic landscape of India, teenage pregnancy has become an important public health issue. The present study was conducted to assess the incidence of teenage pregnancy in Berhampur, Odisha and various maternal and neonatal outcomes of these pregnancies. Methods: This observational study was conducted on 564 antenatal mothers aged 16 to 19 years, who from October 2018 to September 2020. Demographic information of the mothers was noted. Maternal complications during antenatal, intrapartum and postpartum period were noted. Neonatal outcomes, mode of delivery, complications and need for intensive care unit admission was noted. The data collected was described in tabulated form. Results: The incidence of teenage pregnancy at our centre was 4%. Of the 564 teenage pregnancies, 214 were anaemic, pregnancy induced hypertension in 74 and 129 had preterm labour. The caesarean section rate was performed in 51.9%, and the most common indications for caesarean section were fetal distress and cephalopelvic disproportion. Of the 553 live births, 1.04% of them weighed <1.5 kg, 29.16% weighed 1.5 till 2.5 kg, 65.5% weighed between 2.5 to 3.5 kg and 5.2% weighed >3.5 kg. NICU admission was required for 26.9% of the neonates and the most common complication was neonatal jaundice, which was observed in 14.3%. Conclusions: Teenage pregnancies represent a high-risk. The present study demonstrated the various maternal as well as neonatal complications in teenage pregnancies. Those who experience teenage pregnancy should be given extra attention and care.